Peranan Kepemimpinan Kepala Desa Dalam Meningkatkan Kinerja Pemerintahan Desa Hilimbowo Idanoi Kecamatan Gunungsitoli Idanoi - Marniwati Laoli; Fatolosa Hulu; Meiman Hidayat Waruwu; Jeliswan BIJ Gea (LPPM Universitas HKBP Nommensen, 2024)
The Leadership Role of the Village Head in Improving the Performance of the Hilimbowo Idanoi Village Government, Gunungsitoli District. Thesis. Supervisor Fatolosa Hulu, S.E., M.M This study aims to analyze the Leadership of the Village Head, as the initial argument in this study, that the village apparatus and the village head are the lowest base of community services. The quality of services provided depends not only on the performance of the village officials as subordinates, but also on the leader. A person's leadership will determine the progress or decline and the life or death of the organization he leads. The village government, like the central and local governments, is required to provide maximum services for the community and be able to answer the increasing demands of the community, both in terms of quality and quantity. Given the importance of leadership as a determining factor in the success or failure of an organization and business, this study aims to see how the leadership efforts of the Village Head in improving the productivity of the Apparatus performance and how the relationship between the leadership of the Village Head in improving the productivity of the Village Government performance in Hilimbowo Idanoi Village, Gunungsitoli Idanoi District, Gunungsitoli City. The research method used is descriptive qualitative analysis. The informants in this study were the village head and all government officials of Hilimbowo Idanoi Village. Data collection was carried out using interview, observation and documentation techniques. In this study, researchers tried to describe each answer given by the informant during the interview. The results showed that the Hilimbowo Idanoi Village Head had carried out the role of building interpersonal relationships, the role of dealing with information and the role of making decisions in improving the performance of the Hilimbowo Idanoi Village government, Gunungsitoli Idanoi District. Education, work experience and discipline of village officials are factors that influence the performance itself. So it can be concluded that the Hilimbowo Idanoi Village Head has carried out his duties as a leader in improving the performance of the Hilimbowo Idanoi Village government. The roles performed are the role of building interpersonal relationships, the role of dealing with information and the role of making decisions.